2019
DOI: 10.6007/ijarbss/v9-i9/6464
|View full text |Cite
|
Sign up to set email alerts
|

Internal Factors Affecting Continuous Donations among Cash Waqf Donors

Abstract: Cash waqf has a great potential as one of Islamic innovation financial instrument to alleviate the poverty and increase socio-economic in the society. Studies into the factors contributing to the charity among public or first donation are abound. However, the factors effecting donor continuous donation or repeat donation have not yet received significant attention within the academic community. Therefore, this study aimed to identify the internal factors affecting donor's motivation to continuous donation amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 24 publications
2
1
0
Order By: Relevance
“…The outcomes also showed that trust represents a key factor for increasing cash waqf collections, and this is in agreement with prior research (Shih and Fang, 2004;Johari et al, 2015;Osman et al, 2016;Kassim et al, 2019). Trust can be gained when the institutions which collect the funds share information about the way the funds are distributed and the benefits provided to the society.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The outcomes also showed that trust represents a key factor for increasing cash waqf collections, and this is in agreement with prior research (Shih and Fang, 2004;Johari et al, 2015;Osman et al, 2016;Kassim et al, 2019). Trust can be gained when the institutions which collect the funds share information about the way the funds are distributed and the benefits provided to the society.…”
Section: Discussionsupporting
confidence: 89%
“…Prior research has also confirmed that trust has a positive impact on cash waqf collections (Melendéz, 2001;Johari et al, 2015;Shukor et al, 2017;Kassim et al, 2019;Nor and Hashim, 2020). Based on the above discussions, the following hypothesis is presented: H2.…”
Section: Trustmentioning
confidence: 89%
“…The same principle applies to the relationship between waqf institutions and their waqifs. This is in line with a study by Kassim et al (2019) which stated that trust is one of the internal factors that can influence the desire of waqifs (donors) to continuously donate their money to waqf institutions. Therefore, waqf institutions need to make various efforts to foster public trust which can then create a commitment from waqifs to continue to channel their funds to the institutions.…”
Section: Strategic Recommendations That Can Be Provided To Waqf Manag...supporting
confidence: 89%
“…From the legal perspective, waqf is a holding certain property, preserving it for the confined benefit of certain philanthropy and prohibiting any use or disposition of it outside its specific objective (Kahf, 2003). The word waqf in Islamic Law is refer to the contribution intended for religious purpose, family welfare, charity and other things for the sake of Allah (Kassim, 2019). According to Kahf (1999) a waqf is defined as holding a property (e.g.…”
Section: Understanding Waqfmentioning
confidence: 99%
“…Trust therefore remains a foundation of waqf institutions because it paves way for people to donate if they feel satisfy that the money given will be managed in an accountable and transparent manner (Anwar et al, 2017;Kasri & Chaerunnisa, 2021;Tonkiss & Passey, 1999;Torres-Moraga, Vásquez-Parraga, & Barra, 2010;Kassim et al, 2019). In fact, trust is far more important in charity organizations like waqf institutions than other factors because people commit their resources to only trusted charity institutions (Anwar et al, 2017;Kasri & Chaerunnisa, 2021;Kassim et al, 2019). It is described that the element of trust plays a crucial role in determining Muslim donors" willingness to engage in cash waqf giving behaviour (Sargeant & Lee, 2004).…”
Section: Trust and Waqf Contributionmentioning
confidence: 99%